Analytical reading of values and stances included in the second-generation educational curricula- Primary education curricula as a model - Khatout, Ramdhane (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
Our current study seeks to addressing one of the most important values included in the curricula of primary education, or so-called second-generation curricula, where we will try to identify the most important values that constituent the values field , one of the fields of the establishment of these curricula , this field in which the selection of values and their application, It is a source to guide the educational system properly, as well as to ensure that the outputs are saturated with a solid value system, in main fields, the most important of which is national identity as well as citizenship. Therefore, we will try through our study to address the most important values and stances contained in the features of graduation from the primary education in the curricula of the second generation educational. Our study concluded the importance of values in educational curricula, especially with regard to the primary stage. The values of identity and citizenship, as well as humanity, are among the values that the learner must acquire and work them. Therefore, our study recommended the need to pay attention to teaching these values and allocate a certain time for that, so that the student can acquire them.